Performance of Electrochemical Processes in the Treatment of Reverse Osmosis Concentrates of Sanitary Landfill Leachate - Annabel Fernandes; Oumaima Chamem; Maria José Pacheco; Lurdes Ciríaco; Moncef Zairi; Ana Lopes (Molecules, 2019)
Electrochemical technologies have been broadly applied in wastewaters treatment, but few studies have focused on comparing the performance of the different electrochemical processes, especially when used to treat highly-polluted streams. The electrochemical treatment of a reverse osmosis concentrate of sanitary landfill leachate was performed by means of electrocoagulation (EC), anodic oxidation (AO) and electro-Fenton (EF) processes, and the use of different electrode materials and experimental conditions was assessed. All the studied processes and experimental conditions were effective in organic load removal. The results obtained showed that EC, with stainless steel electrodes, is the cheapest process, although it presents the disadvantage of sludge formation with high iron content. At high applied current intensity, AO presents the best treatment time/energy consumption ratio, especially if the samples’ initial pH is corrected to 3. However, pH correction from natural to 3 deeply decreases nitrogen-containing compounds’ removal. For longer treatment time, the EF process with a carbon-felt cathode and a BDD anode, performed at natural iron content and low applied current intensity, is the most favorable solution.